Emerging Readers: Systematic Exploration of Effective English Reading Strategies for Preschoolers - Idris, Mariam Oluwatoyin; Mustafa, Mazlina Che; Wong, Kung-Teck; Bamiro, Nurudeen Babatunde; Olohunfunmi Ismail, AbdulFatai (Pedagogika, 2024)
This study reviews methods for improving preschoolers’ phonological awareness and English reading abilities from 2013 to 2023 using the PRISMA protocol. Analysing 22 articles, it identifies 11 strategies for reading development and 5 for phonological awareness. An interactive reading model is introduced, providing a unified framework to support early childhood educators in enhancing literacy skills in young learners.